Hierarchical porous carbons with controlled micropores and mesopores for supercapacitor electrode materials - Xia, Kaisheng; Gao, Qiuming; Jiang, Jinhua; Hu, Juan (Carbon (New York), 2008)
Various porous carbons were prepared by CO 2 activation of ordered mesoporous carbons and used as electrode materials for supercapacitor. The structures were characterized by using X-ray diffraction, transmission electron microscopy and nitrogen sorption at 77 K. The effects of CO 2 treatment on their pore structures were discussed. Compared to the pristine mesoporous carbons, the samples subjected to CO 2 treatment exhibited remarkable improvement in textural properties. The electrochemical measurement in 6 M KOH electrolyte showed that CO 2 activation leads to better capacitive performances. The carbon CS15A6, which was obtained after CO 2 treatment for 6 h at 950 °C using CMK-3 as the precursor, showed the best electrochemical behavior with a specific gravimetric capacitance of 223 F/g and volumetric capacitance of 54 F/cm 3 at a scan rate of 2 mV/s and 73% retained ratio at 50 mV/s. The good capacitive behavior of CS15A6 may be attributed to the hierarchical pore structure (abundant micropores and interconnected mesopores with the size of 3–4 nm), high surface area (2749 m 2/g), large pore volume (2.09 cm 3/g), as well as well-balanced microporosity and mesoporosity.